2003
DOI: 10.3171/foc.2003.15.3.15
|View full text |Cite
|
Sign up to set email alerts
|

Is spinal instrumentation a risk factor for late-onset infection in cases of distant infection or surgery?

Abstract: As a cause of revision spinal surgery, spinal epidural abscess after instrumentation-assisted fusion is rare in neurosurgical practice. Postoperative infections are frequently seen in the time period soon after surgery. The authors report on the case of a 45-year-old woman who had undergone posterior instrumentation-augmented fusion for L4–5 degenerative spondylolisthesis. Ten months after the operation she presented to the neurosurgery clinic with complaints of severe low-back pain an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Tissue perfusion may be damaged as a result of surgical trauma, rendering eradication of the microorganisms colonized on the fixators more difficult. 1,12 Some authors have reported that a 6-to 8-week course of specific antibiotics and surgical evacuation of the dead tissues with irrigation usually suffice to bring the infection under control. 1,13 Some have advocated the routine removal of bone grafts and instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue perfusion may be damaged as a result of surgical trauma, rendering eradication of the microorganisms colonized on the fixators more difficult. 1,12 Some authors have reported that a 6-to 8-week course of specific antibiotics and surgical evacuation of the dead tissues with irrigation usually suffice to bring the infection under control. 1,13 Some have advocated the routine removal of bone grafts and instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Although the incidence of deep spinal infection following surgery is about 0.9% to 1.9% it increases to 3.6% with the use of instrumentation alone, and to 2.4% to 7.5% with instrumentation and graft fusion together. 4,11,12 Upon diagnosing bilateral psoas abscesses, in conjunction with a midline subcutaneous abscess, the decision was made to leave most of the instrumentation in place. The bilateral intertransverse grafts were removed.…”
Section: Discussionmentioning
confidence: 99%
“…Muckley et al [21] reported on six cases of psoas abscess as a special complication after spine surgery. Naderi et al [22] reported on a case of a combined epidural and psoas abscess 10 months after posterior instrumentation in a female patient who developed severe back pain after having undergone laparoscopic cholecystectomy 1 month prior to readmission.…”
Section: Discussionmentioning
confidence: 99%